Bacterial identification using PCR-DGGE in milk of mastitic cows from a herd of crossbreed GYR-Holstein: Municipio Obispo Ramos de Lora, Merida. Venezuela (Ágora de Heterodoxias, 2015)
In order to characterize the composition of bacteria in samples of milk from crossbreed Gyr–Holstein cows affected with mastitis, from a herd with a history of clinical mastitis from six months ago and low milk production, a culture-independent  PCR - DGGE technique using as a marker the V3 region 16S rDNA was carried out. The assessment of sub clinical mastitis was performed by CMT. Samples were taken from cows that had a least 4 weeks without antibiotic therapy, and aliquots were used for bacteriology and molecular identification. Only culture negative samples were selected for PCR - DGGE. The level of sub clinical mastitis by CMT at the moment of sampling was 48.07 % (225 quarter). PCR-DGGE, revealed the presence of several types of bacteria in the samples studied, which were more closely related to bacteria of the Firmicutes and Proteobacteria phylum, which highlight the presence of the genus Acinetobacter. Most of these microorganisms are involved in antibiotic multi-resistance, so the technique becomes a useful tool for analyzing these microbial populations in cows with clinical mastitis and negative culture and establish better recommendations for control and prevention of this pathology in dairy farms. Others researches are needed to determine the implications of microorganisms isolated in this work over animal and human health.
Keywords: bacteria; mastitis; negative culture; PCR-DGGE